Implementasi Etika Bisnis Dalam Operasi UKM di Era Digital - Abdulah Rakhman; Bernadine Bernadine; M. Fuad; Liaw Bun Fa (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2022)
When a business is faced with extreme competition, the ability of SMEs to maintain its market is needed in various ways to excel in the competition. Business ethics in a company has a very important role in running its business. A company will succeed based not only on good morals and management but also on good business ethics. The problem is that unethical behavior in business activities often occurs due to the development of digital-based information technology which provides opportunities, weak morals, and awareness of ethics in doing business, making opportunities for business actors to commit acts that violate business ethics. Starting from this problem, the Kwik Kian Gie Institute of Business and Informatics teaching group conducted training and mentoring for members of the Garudayaksa Nusantara Cooperative on the Implementation of Business Ethics in SME operations which was held on July 22, 2022, in Jakarta. The purpose of this training and mentoring is to increase understanding of Business Ethics and general principles of Business Ethics, provide insight into the implementation of Business Ethics in SME Operations, Provide examples of violations of business ethics in SME operations in the digital era, and motivate SME business people to implement Business Ethics. It is hoped that this training will result in the formation of awareness among SMEs about the importance of business ethics in relation to the company's goals for long-term profits, and the development of ethical behavior among SMEs in business operations in the digital.